Review of Footsteps on the ice: the Antarctic diaries of Stuart D. Paine, Second Byrd Expedition, by M.L. Paine - Baughman, Timothy H (Polar Research, 2008)
If the reader is looking for another rehashing of one of the adventures of the “Heroic Era” of Antarctic exploration, or another reshaping of the same old material about the three or four explorers from that period who get all the attention, M.L. Paine’s Footsteps on the ice: the Antarctic diaries of Stuart D. Paine, Second Byrd Expedition is not the book for you. But if you are a serious Antarctic buff who wants to learn something new, and really get inside one of the early expeditions of the 20th century, Paine’s volume will be a compelling read.
Keywords: Antarktis; Richard Evelyn Byrd; Sydpolflyvningen; bokanmeldelser; dagbøker; ekspedisjoner; fly; luftfart; oppdagelsesreiser; polarflyving; turisme

Flykatastrofe i antarktisk "white out" - Dannevig, Petter (Været: populærvitenskapelig tidsskrift, 1985)
Keywords: Antarktis; luftfart

Antarctic spotters - Walford, G Brian (Norsk Luftmilitært Tidsskrift, 1951)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; flygning; luftfart

Air reconnaissance in Antarctica - Walford, G Brian (ESSO Air World, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flygning; luftfart